PENGARUH PENGGUNAAN MEDIA FILM ANIMASI KARTUN TERHADAP KEMAMPUAN MENULIS KARANGAN NARASI SISWA KELAS IV SD NEGRI 25 PALEMBANG: - Intan Permata Sari; Nuranisa; Robert Budi Laksana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to address issues related to the teaching of Indonesian language, specifically in the subject of “Writing Narrative Essays” for fourth-grade students. The problem arises due to several factors, including the teacher relying solely on LKS (student worksheets) and textbooks as the only learning tools. This has led to a lack of student interest and boredom during Indonesian language lessons. Assessment results show that 49% of students did not reach the minimum mastery criteria (KKTP). Therefore, students need appropriate learning media.This research employs a quantitative method with a quasi-experimental design. There are two variables in this study: variable "X" (Animated Film Media) and variable "Y" (Narrative Essay Writing Skills). The study began with an instrument validation process, in which 10 questions were initially prepared and 5 were selected for trial testing. The trial results indicated that all five questions were valid, highly reliable, and considered.